Revealing the Meaning of Accounting Practices in the Passolo Money Tradition of the Makassar Tribe - Sri Depi; Alimuddin; Syarifuddin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research aims to reveal the meaning of accounting practices contained in the Money Passolo tradition of the Makassar Tribe in South Sulawesi. The Passolo Money Tradition is the practice of giving money donations mutually during various traditional ceremonies, especially weddings and deaths. Using an ethnographic approach, this research explores how the Makassar community interprets and manages money flows in this tradition from a social and cultural accounting perspective. The research method used is ethnography with data collection techniques through participant observation, in-depth interviews and analysis of cultural documents. Informants were selected using purposive sampling, consisting of traditional leaders, community leaders, traditional practitioners, and family members who actively carry out the Uang Passolo tradition. Data were analyzed using thematic analysis based on cultural phenomenology. The research results show that Money Passolo contains rich and complex accounting dimensions. There is an informal recording system based on collective memory and communal records that function as a social ledger. This practice contains the values ​​of social accountability, reciprocity and solidarity. The accounting meaning of Passolo Money goes beyond mere financial calculations, but rather becomes an instrument for maintaining social relations, a marker of status, and an expression of the values ​​of Siri' na Pacce which is the life philosophy of the Makassar people. This research contributes to the development of accounting science that is more inclusive of cultural diversity, especially in the context of Indonesia's indigenous communities.